2012
DOI: 10.1002/jmri.23579
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of intersubject variability of cerebral blood flow measurements using MRI and positron emission tomography

Abstract: Purpose: To investigate the within and between subject variability of quantitative cerebral blood flow (CBF) measurements in normal subjects using various MRI techniques and positron emission tomography (PET). Materials and Methods:Repeated CBF measurements were performed in 17 healthy, young subjects using three different MRI techniques: arterial spin labeling (ASL), dynamic contrast enhanced T1 weighted perfusion MRI (DCE) and phase contrast mapping (PCM). All MRI measurements were performed within the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
100
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(124 citation statements)
references
References 33 publications
17
100
1
2
Order By: Relevance
“…23,34 Metabolic Basis of Between-Subject Variability Previous studies show a very similar between-subject variability in healthy young subjects with between-subject coefficient of variation of 16% using the Kety Schmidt technique 1 and of 15% to 20% using various magnetic resonance imaging and positron emission tomography methods. 4 Relative between-subject variability in the present study was B13%. These figures are very similar to the coefficient of variation of 13% of both CMRO 2 and neuron density reported in brains of healthy subjects.…”
Section: Study Limitationsmentioning
confidence: 41%
See 1 more Smart Citation
“…23,34 Metabolic Basis of Between-Subject Variability Previous studies show a very similar between-subject variability in healthy young subjects with between-subject coefficient of variation of 16% using the Kety Schmidt technique 1 and of 15% to 20% using various magnetic resonance imaging and positron emission tomography methods. 4 Relative between-subject variability in the present study was B13%. These figures are very similar to the coefficient of variation of 13% of both CMRO 2 and neuron density reported in brains of healthy subjects.…”
Section: Study Limitationsmentioning
confidence: 41%
“…The model is explained in more details in a previous publication. 4 Within-subject variability (or test-retest variability) includes both random method imprecision and true within-subject variability, whereas between-subject variability reflects the true variability of CBF and systematic (or subject-specific) errors. These two variance components were entered as random effects in the model.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found moderate to good correlations (r ϭ 0.4 -0.8) between pseudocontinuous ASL and PET imaging for pCBF measurements. 4,27,28 On the contrary, Henriksen et al 29 showed a large underestimation of ASLbased pCBF (75%) compared with the estimation by PCMRI and no correlation between the 2 methods. One explanation for this result might be that they used a model-free pulsed-ASL method.…”
Section: Discussionmentioning
confidence: 91%
“…51 The average CBF in the control cohort is somewhat higher than the CBF values reported in young adults using arterial spin labeling. 52 Cerebral blood flow displayed significant intersubject variability, with even the healthy controls spanning a range of almost 30 to 60 mL per minute per 100 g. Since the outcome of interest is the difference between the two patient samples (TBI and control subjects), we did not conduct paired analysis. Future studies will address this limitation to study individual patient changes in metabolism over time after TBI.…”
Section: Discussionmentioning
confidence: 99%